New Perspectives on Classical Meanness of Some Ladder Graphs - A. M. Alanazi; G. Muhiuddin; A. R. Kannan; V. Govindan (Journal of Mathematics)
In this study, we investigate a new kind of mean labeling of graph. The ladder graph plays an important role in the area of communication networks, coding theory, and transportation engineering. Also, we found interesting new results corresponding to classical mean labeling for some ladder-related graphs and corona of ladder graphs with suitable examples.